The Village Dinosaur - "Arkle, Phyllis" (Puffin Books: Harmondsworth, 1979)
Jed Watkins is delighted when local quarrymen discover a dinosaur buried in their quarry. The men pull the beast out and Jed makes friends with it at once.
Keywords: Dinosaurs Fiction